PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI, MODAL USAHA, DAN E-COMMERCE TERHADAP KINERJA UMKM DI KABUPATEN LUWU - Nengsi Nengsi; Rifqa Ayu Dasila; Mutmainna Mutmainna (Jurnal Riset Terapan Akuntansi, 2026)
The study aims to examine the effect of the implementation of Accounting Information Systems, Business Capital, and E-commerce on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in Luwu Regency. The approach used is quantitative, the study population is 8,539 MSMEs registered at the Cooperatives and SMEs Office of Luwu Regency. The sample size is determined using the Slovin formula, obtaining a sample size of 86 respondents. The sampling technique is purposive random sampling, Data were obtained through the distribution of questionnaires compiled based on the indicators of each research variable. The results of the study indicate that the implementation of accounting information systems, business capital, and e-commerce have a positive effect on improving MSME performance. This indicates that the better the implementation of accounting information systems, the stronger the capital support, and the more optimal the use of e-commerce, the higher the performance of MSMEs achieved. Keywords: Accounting Information System, Business Capital, E-commerce, MSME Performance, Luwu Regency.